Prediction of residue coke content and operating modes of regenerator in the catalytic cracking technology - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Shafran T. A. Tatjyana Aleksandrovna; Oreshina A. A. Aleksandra Aleksandrovna; Seytenova G. Zh. Gayni Zhumagalievna (2020, 2020)
Title screen